Solriamfetol for Excessive Sleepiness in Narcolepsy and Obstructive Sleep Apnea. Issue 10 (October 2020) - Powell, Jason; Piszczatoski, Chris; Garland, Scott
Objective: The purpose of this article is to review the available clinical trial data that led to the Food and Drug Administration (FDA) approval of solriamfetol as well as its role in clinical practice. Data Sources: A MEDLINE/PubMed search was conducted (January 2000 to February 2020) using the keyword solriamfetol to discover appropriate clinical trials. Study Selection and Data Extraction: Articles were included that were published in the English language and related to the FDA approval of solriamfetol or provided novel information regarding this drug entity. Data Synthesis: The findings of the review show that solriamfetol may be a safe and effective option for the treatment of excessive sleepiness (ES) related to narcolepsy and obstructive sleep apnea (OSA). Relevance to Patient Care and Clinical Practice: Solriamfetol is distinguished from other stimulants in that it has lower binding affinity to dopamine and norepinephrine transporters and does not have the monoamine-releasing effects of amphetamines at usual therapeutic doses. Because of solriamfetol's unique mechanism of action, there may be a reduction in abuse potential compared with the other currently FDA-approved options. Conclusions: In clinical trials, solriamfetol has shown dose-dependent improvement in wakefulness over placebo and adds another option for clinicians when treating ES in narcolepsy and OSA.